Mobile app for trilingual Islamic banking & finance terms - Dollah, Nafi@Hanafi (2018)
The current project proposes the extension of the previous project to be represented in electronic form via mobile applications (app). The present research seeks to shed some light on the workable model for using and developing this app in a more convenient way via devices such as iPhone, iPad or any Android-based smart devices. It tends to explore further the prototype development and implementations of the mobile accessibility using commonly used mobile platforms i.e. iOS and Android. It is wise to note here that the mobile app for Islamic banking and financial glossary of terms is none to be found in the market nowadays.